The association between pregnancy outcomes and frozen-thawed embryo transfer cycles based on D3 cell count in high-quality blastocysts - Li, Xiang; Zeng, Youman; Zhu, Lingling; Yang, Zengyu; Luo, Yudi; Jia, Jun-Long (Frontiers in Endocrinology, 2024)
Objective: To investigate the number of cells in D3-stage embryos of high-quality blastocysts as a contributing factor, to evaluate the clinical pregnancy outcomes in frozen-thawed embryo transfer cycles, and to determine the impact of D3-stage cell count on pregnancy outcomes. Methods: Patients under 38 years old who underwent frozen-thawed single high-quality blastocyst transfer at our center were selected. Based on the cell count of D3 cleavage-stage embryos forming blastocysts, patients were divided into three groups: ≤6 cells, 7-9 cells, and ≥10 cells. A multivariate regression analysis was used to establish the prediction model, analyzing the impact of different D3 cleavage-stage cell counts on clinical pregnancy outcomes to guide clinical laboratories in selecting blastocysts with the best pregnancy outcomes for transfer. Results:. This study identified a significant association between D3 cell count, blastocyst development stage, and embryo age. Embryos with a higher D3 cell count (≥10) were more likely to reach advanced blastocyst stages and form blastocysts by D5, whereas embryos with fewer D3 cells (≤6) were more likely to form blastocysts on D6. While D3 cell count significantly influenced blastocyst stage and timing of embryo development, no significant differences were observed between groups regarding clinical pregnancy, implantation, or live birth rates. Notably, embryos with fewer D3 cells exhibited a significantly lower miscarriage rate than other groups. Multivariate regression analysis showed a significant correlation between blastocyst stage, embryo age, and D3 cell count, particularly in D5 embryos and more advanced blastocysts. The increased miscarriage rate may be related to lower D3 cell count, and inadequate endometrial preparation was associated with poorer pregnancy outcomes. The type of infertility was also linked to D3 cell count, with secondary infertility patients showing more significant influencing factors. Conclusion: D3 cell count and related factors play a critical role in pregnancy outcomes during frozen-thawed high-quality blastocyst transfer cycles. Optimizing embryo age, selecting blastocysts at different stages, and refining endometrial preparation protocols are likely to enhance clinical pregnancy and live birth rates.